COVID-19 and the Swedish Labor Market in 2021, the Second COVID-19 Year - Fredrik W. Andersson; Eskil Wadensjö (Institute of Labor Economics (IZA), 2022)
The pandemic has mainly affected the state of health and mortality, but has also had effects on the economy and the labor market. This article reports the development of the total number of employees, their distribution by sectors and regions and the changes in the number of employees for different groups in 2021 compared with 2019 in Sweden. We do not deal with the development of the number and composition of the self-employed. We also do not go into the development of employees' conditions in terms of wages, working hours and working environment. However, we study something that is in focus for the general debate: How was the development of the number of employees and their composition in 2021, "the second year of the pandemic"? The main result is that we find large differences in the development for different groups. The most surprising is the positive development of the number of foreign-born employees.
Keywords: I15; J15; J21; J23; J61; 330; Swedish labor market; COVID-19; employment; migrants